2017
DOI: 10.7717/peerj.3728
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of N-terminus and two internal amino acids is dispensable for degradation of a protein that aberrantly engages the endoplasmic reticulum translocon

Abstract: Conserved homologues of the Hrd1 ubiquitin ligase target for degradation proteins that persistently or aberrantly engage the endoplasmic reticulum translocon, including mammalian apolipoprotein B (apoB; the major protein component of low-density lipoproteins) and the artificial yeast protein Deg1-Sec62. A complete understanding of the molecular mechanism by which translocon-associated proteins are recognized and degraded may inform the development of therapeutic strategies for cholesterol-related pathologies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 66 publications
(101 reference statements)
0
6
0
Order By: Relevance
“…Roles for Hrd1 and Ste24 in TQC have been inferred by their ability to target unique model substrates engineered to aberrantly engage the translocon. Hrd1 substrates are incompletely stabilized in hrd1D yeast, suggesting parallel degradative mechanisms (19). To query their specificity in TQC, we asked if Hrd1 and Ste24 can target characterized substrates of the other enzyme.…”
Section: Hrd1 and Ste24 Possess Overlapping Substrate Specificitymentioning
confidence: 99%
See 1 more Smart Citation
“…Roles for Hrd1 and Ste24 in TQC have been inferred by their ability to target unique model substrates engineered to aberrantly engage the translocon. Hrd1 substrates are incompletely stabilized in hrd1D yeast, suggesting parallel degradative mechanisms (19). To query their specificity in TQC, we asked if Hrd1 and Ste24 can target characterized substrates of the other enzyme.…”
Section: Hrd1 and Ste24 Possess Overlapping Substrate Specificitymentioning
confidence: 99%
“…Cycloheximide chase experiments (48), cell lysis, western blotting (49,50), and endoglycosidase H (Endo H; New England Biolabs) treatment (19) were performed as described. The following antibody dilutions were used: mouse anti-HA.11 (Clone 16B12; BioLegend) at 1:1,000 to detect Clogger; mouse anti-c-myc (Clone 9E10; BioLegend) at 1:1,000 to detect sec61-13myc; and mouse antiphosphoglycerate kinase 1 (Pgk1; clone 22C5D8; Thermo Fisher Scientific) at 1:20,000.…”
Section: Cycloheximide Chase Cell Lysis Endoglycosidase H Treatmentmentioning
confidence: 99%
“…These mutations did not affect Hrd1-mediated degradation of Deg1-Sec62 suggesting that glycosylation was not required for degradation [10]. Degradation of variants of Deg1*-Sec62 with mutated acetylation sites showed that acetylation was also not required for Hrd1-dependent degradation of Deg1*-Sec62 [25]. There may be uncharacterized PTMs that contribute to Deg1-Sec62 degradation, but there is no evidence to suggest so.…”
Section: How Does Er Stress Impair Erad-t?mentioning
confidence: 95%
“…ER stress does not inhibit Hrd1 function directly, since degradation of some Hrd1-targeted proteins (such as ERAD-M substrates) is unaffected by ER stress. While ER stress impairs modification of translocon-clogging proteins [45] this is likely not the reason for impaired degradation, since it has been shown modifications are not required for degradation [10,25]. Inhibition of ERAD-L by ER stress is likely to occur by saturation of the multifunctional ER chaperone Kar2 [7]; Kar2 overexpression partially rescues impaired ERAD-L during conditions associated with elevated ER stress [38].…”
Section: Er Stress and Erad-tmentioning
confidence: 99%
See 1 more Smart Citation